JNK Mediates Differentiation, Cell Polarity and Apoptosis During Amphioxus Development by Regulating Actin Cytoskeleton Dynamics and ERK Signalling - Somorjai, Ildiko M. L.; Ehebauer, Matthias T.; Escrivà, Hector; Garcia-Fernàndez, Jordi (Frontiers in Cell and Developmental Biology, 2021)
c-Jun terminal kinase (JNK) is a multi-functional protein involved in a diverse array of context-dependent processes, including apoptosis, cell cycle regulation, adhesion and differentiation. It is integral to a number of signalling cascades, notably downstream of non-canonical Wnt and MAPK signalling pathways. As such, it is a key regulator of cellular behaviour and patterning during embryonic development across the animal kingdom. The cephalochordate amphioxus is an invertebrate chordate model system straddling the invertebrate to vertebrate transition and is thus ideally suited for comparative studies of morphogenesis. However, next to nothing is known about JNK signalling or cellular processes in this lineage. Pharmacological inhibition of JNK signalling using SP600125 during embryonic development arrests gastrula invagination and causes convergence extension-like defects in axial elongation, particularly of the notochord. Pharynx formation and anterior oral mesoderm derivatives like the preoral pit are also affected. This is accompanied by tissue-specific transcriptional changes, including reduced expression of six3/6 and wnt2 in the notochord, and ectopic wnt11 in neurulating embryos treated at late gastrula stages. Cellular delamination results in accumulation of cells in the gut cavity and a dorsal fin-like protrusion, followed by secondary Caspase3-mediated apoptosis of polarity-deficient cells, a phenotype only partly rescued by co-culture with the pan-caspase inhibitor Z-VAD-fmk. Ectopic activation of ERK signalling in the neighbours of extruded notochord and neural cells, possibly due to altered adhesive and tensile properties, as well as defects in cellular migration, may explain some phenotypes caused by JNK-inhibition. Overall, this study supports conserved functions of JNK signalling in mediating the complex balance between cell survival, apoptosis, differentiation and cell fate specification during cephalochordate morphogenesis.